An Investigation into the Use of an Optimal Grouping Procedure in Land Use Capability Analysis, Pichincha Province, Ecuador - Batchelor , Bruce Edward (My University, 1971)
The study concerns the development of a methodology which will allow the rating of soil or land units in view of their sustained economic capacity. Some literature is surveyed to show that no known scheme justifies statistically the number of classes used;many schemes avoid the use of empirical crop yield data altogether. The factor analysis of farm activities and crop yield data will provide a set of scores, incorporating the important variables only, which may be grouped by the statistical method ·which is the core of the work. The Andean portion of the Province of Pichihcha, Ecuador, was the area studied. A number of farm types were discovered, differentiated by levels of investment and subsequently by type of activity. The strong crop yield/environmental correlations needed to create an improved land use capability scheme were found not to exist, but some important observations were made upon the profitability of the crop holdings and the fertility status of the soils. A number of land types with regional tendencies were found.
Keywords: methodology; development; soil; land; economic; crop yield; farm activities